Analisis Potensi Solar Cell pada Gedung I Universitas Pembangunan Panca Budi - Muhammad Erpandi Dalimunthe; Zulkarnain Lubis; Eddy Sutejo; Dwi Permata Sari (Fidelity : Jurnal Teknik Elektro, 2023)
Solar thermal energy is very abundant in areas that have a tropical climate such as in North Sumatra Province which is always exposed to sunlight throughout the year. It is a source of energy that has the potential to be developed. Solar Power Plants (PLTS) generate electricity from solar cells that are exposed to sunlight. The high and low voltage generated depends on the amount of sunlight hitting the solar cell panel. Building I of Pembangunan Panca Budi University uses a source of electrical energy from PT. PLN as the only primary source to run all the facilities in the building. The obstacle that is often experienced is when there is a blackout or cessation of the supply of electrical energy from PLN. All equipment that uses electrical energy stops working due to the absence of electricity.The research method is to collect data in the field, analyze the collected data and analyze the factors that influence the intensity of the sun. The number of solar cell panels used is 189 units with a capacity of 250 Wp with the area required for solar cell panel installation is 189 x 1.7 = 321.3 mÂ². The use of solar cells as a source of New, Renewable Energy (EBT) is one of the alternative energy sources which is expected to be able to meet the demand for electrical energy in Building I Pembangunan Panca Budi University.